Application of single-cell sequencing technology to the study of embryonic developmental toxicity of emerging contaminants: Progress and perspectives - Weizhao CAO; Yunhui ZHANG (环境与职业医学)
Emerging pollutants are a class of environmental chemicals characterized by bioaccumulation, environmental persistence, and high toxicity. Their long-term accumulation poses severe threats to the environment and human health. In recent years, single-cell RNA sequencing (scRNA-seq) technology has enabled the analysis of transcriptomes at the single-cell level, revealing cellular heterogeneity and the complexity of intercellular communication. In toxicological studies, scRNA-seq technology has been applied to identify the responses of different cell types to pollutants and to elucidate the mechanisms of pollutant action during embryonic development, providing novel perspectives on the toxicity mechanisms of emerging pollutants. This paper reviewed the classification and characteristics of single-cell sequencing technologies and their applications in investigating the developmental toxicity of emerging pollutants, including perfluorinated and polyfluorinated alkyl substances (PFAS), antibiotics, microplastics, phthalates, and bisphenols. It also discussed the limitations of current studies and proposed future research directions. Through methods such as cellular heterogeneity analysis and pseudotemporal chronological analysis, single-cell sequencing can explore and validate the specific toxicity mechanisms of emerging pollutants in embryonic development. However, challenges remain, including dataset bias, batch effects, and developmental differences between humans and model organisms. Future research should focus on optimizing data analysis methods, integrating multi-omics sequencing data, and exploring the use of human organoid models in toxicological studies. Such efforts will contribute to a more comprehensive understanding of the toxicity mechanisms and long-term health impacts of emerging pollutants, providing a theoretical basis for their stringent regulation and control.